The hippocampus and TNF: Common links between chronic pain and depression. (June 2015) - Fasick, Victoria; Spengler, Robert N.; Samankan, Shabnam; Nader, Nader D.; Ignatowski, Tracey A.
Highlights: We reviewed commonalities between chronic pain and depression. Chronic pain and depression generally occur in concert. The hippocampus is similarly affected by chronic pain and depression. Increased hippocampal TNF production is common in both disorders. Strategies to decrease hippocampal TNF may prove therapeutically efficacious. Abstract: Major depression and chronic pain are significant health problems that seriously impact the quality of life of affected individuals. These diseases that individually are difficult to treat often co-exist, thereby compounding the patient's disability and impairment as well as the challenge of successful treatment. The development of efficacious treatments for these comorbid disorders requires a more comprehensive understanding of their linked associations through common neuromodulators, such as tumor necrosis factor-α (TNFα), and various neurotransmitters, as well as common neuroanatomical pathways and structures, including the hippocampal brain region. This review discusses the interaction between depression and chronic pain, emphasizing the fundamental role of the hippocampus in the development and maintenance of both disorders. The focus of this review addresses the hypothesis that hippocampal expressed TNFα serves as a therapeutic target for management of chronic pain and major depressive disorder (MDD).